Why Is the Vertical-Kilometer of Fully (Switzerland) So Fast? Physiological and Mechanical Benefits of Stair Ascent on Extreme Uphill Slopes - Louis Finiel; Valentin Luc; Tristan Cardillo; Davide Malatesta; Fabio Borrani (Medicine & Science in Sports & Exercise, 2026)
Purpose: The world's fastest vertical kilometer course in Fully (Switzerland) is comprised of stairs at a very steep grade (~31°). The aim was to determine whether stair ascent, with and without poles, lowered physiological, mechanical, and neuromuscular demands compared with continuous uphill ramp locomotion at VK-relevant slopes. Methods: Twenty-two endurance-trained participants completed randomized treadmill trials at a constant vertical speed (800 m·h−1) in three conditions: uphill ramp (R), stairs (S), and stairs with poles (SP), each performed at six slopes (18–38°). Metabolic power (MP), heart rate (HR), minute ventilation (V̇E), rating of perceived exertion (RPE), internal mechanical work, step frequency, and lower-limb electromyography were measured. Results: At 18°, S elicited greater MP (6%), HR (4%), and V̇E (7%) compared to R (all P